Psychomotor Therapy Program of Eye-Hand Coordination Game to Address Hand Flapping Behavior in Children with Autism - Triswandari, Retno; Susetyo, Budi; Widya, Mamad; Ardisal, Ardisal (Department of Special Education, 2024)
This study aims to find out the extent of psychomotoric therapy program of eye-hand coordination games addressing the hand flapping behavior in children with autism. This study was motivated by the frequent emergence of hand flapping behavior in children during learning or playing, while verbal instructions given by the teacher are insufficient to raise children’s awareness. This study was conducted on MB subject, an autistic student of an SDLB. This research used Single Subject Research (SSR), A-B-A design. The results of the study answered the problem formulation proposed because there was an increase in the value of the mean level of children’s motor skills, including the baseline-1 phase (A-1) by 0%, the intervention phase (B) by 33%, and the baseline-2 phase (A-2) by 75%, and a decrease in the value of the mean level of intensity/number of hand flapping behaviors, including the baseline-1 phase (A-1) by 187 times, the intervention phase (B) by 154, and the baseline-2 phase (A-2) by 119 times. Based on these results, it can be concluded that the psychomotor therapy program of eye-hand coordination games can address hand flapping behavior in MB, children with autism.